SAT0418 Anxiety and depression on disease activity and quality of life of spondyloarthritis patients under biologic therapies. (15th June 2017) - Madeira, N; Borges, J; Cardoso, A; Miranda, L; Barcelos, F; Miguel, C; Silva, C; Fernandes, S; Trinca, R; Medeiros, D; Campanilho-Marques, R; Santos, H; et al.
Abstract : Background: Several studies describe an association between anxiety, depression and disease activity in Spondyloarthritis (SpA). Objectives: To assess disease activity and quality of life in anxious and depressed SpA patients. Methods: Observational, retrospective, cross-sectional study of SpA patients on bDMARDs, registered at Reuma.pt, Portuguese Rheumatology registry, with ≥1 clinical evaluation from November 2015 to July 2016. Demographic and clinical outcomes including: BASDAI, BASMI, BASFI, ASDAS, DAS 28–3V ESR in peripheral psoriatic arthritis, tender and swollen 44 joints count (TJC, SJC), patients' pain and global assessments, physician's global assessment, CRP, ESR, ASQoL, EQ-5D, FACIT-F for fatigue and HADS scale with 2 domains, HADS-A for anxiety and HADS-D for depression (a cutoff of 8 defining these symptoms), were collected. Statistics: Mann-Whitney test, p<0.05. SPSS® v.17. Results: 160 patients were included, 41.9% were male, with mean: current age 50.7±11.9, age at diagnosis 36.9±11.96, at 1st bDMARD 46.2±11.8, time from diagnosis 18.5±10.3, years. The mean DAS 28–3V ESR was 3.2±1.4, BASDAI 2.98±2.2, ASDAS 2.4±1.2, BASFI 2.68±2.26, BASMI 3.36±1.7, patient's global assessment 28.8±24.1, physician's global assessment 14.5±15.2, ESR 18.8±18.1 mm/h, CRP 6.7±16.01 mg/L, ASQoL 6.2±5.6, FACIT-F 37.2±10.1 and EQ-5D 0.417±0.19. The mean HADS-A was 5.96±4.01 and HADS-D was 5.05±4.1 (HADS-A≥8 in 39.5% and HADS-D≥8 in 28.3% patients). Comparison of anxious vs non-anxious and depressive vs non-depressive groups appears on table 1 . Conclusions: These results suggest that anxious and depressed patients may have higher disease activity, more functional limitations and worse quality of life. These symptoms should not be underestimated, but instead, they should be controlled to achieve clinical improvement. Disclosure of Interest: None declared